The Regulator of G Protein Signaling Family - De Vries, Luc; Zheng, Bin; Fischer, Thierry; Elenko, Eric; Farquhar, Marilyn G. (Annual Review of Pharmacology and Toxicology, 2000)
Regulator of G protein signaling (RGS) proteins are responsible for the rapid turnoff of G protein–coupled receptor signaling pathways. The major mechanism whereby RGS proteins negatively regulate G proteins is via the GTPase activating protein activity of their RGS domain. Structural and mutational analyses have characterized the RGS/Gα interaction in detail, explaining the molecular mechanisms of the GTPase activating protein activity of RGS proteins. More than 20 RGS proteins have been isolated, and there are indications that specific RGS proteins regulate specific G protein–coupled receptor pathways. This specificity is probably created by a combination of cell type–specific expression, tissue distribution, intracellular localization, posttranslational modifications, and domains other than the RGS domain that link them to other signaling pathways. In this review we discuss what has been learned so far about the role of RGS proteins in regulating G protein–coupled receptor signaling and point out areas that may be fruitful for future research.
Keywords: GAP